Study of the documentary collection of the Real Casa de Beneficencia y Maternidad de La Habana (1830-1898): classification proposal and research sources - Cristóbal Querol, Desireé (Revista General de Información y Documentación, 2025)
The main objective of this work is to present the analysis of the documentary collection produced by the Cuban institution the Real Casa de Beneficencia y Maternidad during the 19th century. Firstly, we identified the producing institution and the documentation produced. Secondly, the classification and the proposal of the classification chart were made based on an intellectual organization, but with the aim of being able to implement it. Finally, it is presented, by virtue of the unpublished documentation found, the sources of research that can be initiated with the information from these "new sources". In short, the purpose of this analysis is to showcase the richness and documentary variety of the collection and to offer the National Archive of Cuba a basic classification chart for the definitive one that will allow, ultimately, the physical arrangement of the documentation under standardized archival criteria.